Evaluasi Pelaksanaan Program Praktik Kerja Lapangan (PKL) di SMK Negeri 2 Toraja Utara - Deddy; Hasanah Nur; Anas Arfandi (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This study aims to evaluate and analyze the implementation of the Prakerin Program at SMK Negeri 2 Toraja Utara and to identify the factors that influence the success of the program. This research is a qualitative research using the CIPP model evaluation. Data was collected through observation, interviews and document study. The research respondents consisted of PKL supervising teachers, street vendor participant students, and related parties at school. The results of the study show that (1) context aspects: vision and mission have been translated into the formulation of graduate competencies, objectives have not been fully achieved, the curriculum has been synchronized with market needs by involving IDUKA, (2) input aspects: implementation strategy, placement procedures, scheduling and budget management has been carried out according to procedures, communication with IDUKA has been improved, (3) Process aspects: implementation has been according to procedures only monitoring has been intensified, (4) Product aspects: good results, street vendors program is beneficial to students, schools and IDUKA, impact the street vendors program has not been significant for graduate absorption, cooperation with IDUKA needs to be improved. North Toraja 2 Public Vocational School has not yet carried out a thorough evaluation of the implementation of the street vendors program. This research is expected to provide useful input for SMK Negeri 2 Toraja Utara in improving the quality and effectiveness of the implementation of the street vendors program. In addition, this research can also be a reference for other vocational education institutions in optimizing the PKL Program in order to prepare students to enter the world of work.